Marshall Asphalt Mix and Superior Performance Asphalt Mix in Oman: A Comparative Study - Al Kaaf, Khalid; Ibeabuchi, Victor Tochukwu (Engineering, Technology & Applied Science Research, 2023)
The mix design procedure used in Superior Performance Asphalt Pavements (Super-pave) was created by the Strategic Highway Research Program (SHRP) in response to the limitations and empirical approach of Marshall methodology. This study aims to compare the Marshall asphalt mixture design method with the Super-pave asphalt mixture design procedures. Locally available aggregates commonly used in asphalt concrete mixtures in Oman were used. The asphalt mixtures were made with aggregate and asphalt-binder with a penetration grade of 60/70 and PG 64-10. Samples from two mixes were made accordingly. Volumetric properties analysis, flow, Marshall stability, and loss of Marshall stability tests were carried out. According to the study findings, the optimum asphalt composition was 4.5% when utilizing the Marshall methodology and 5.5% when using the Super-pave approach. Furthermore, the Super-pave specimens showed less loss of Marshall stability (22.22%) than the Marshall specimen (30.09%).